Taxonomic study of wasp species in the Polybia (Myrapetra) occidentalis group morphologically related to P. scrobalis and P. flavifrons, with description of a new species (Hymenoptera, Vespidae, Polistinae) - Amorim, Danielle C. De A.; Junior, José N. A. Dos Santos; Filho, Fernando Da S. Carvalho–; Silveira, Orlando T.; Carpenter, James M. (Zootaxa, 2024)
Polybia is a genus of neotropical swarming wasps, and the largest within the Epiponini (Vespidae). The genus is dominant in the Neotropics, with more than 59 described species and eleven recognized subgenera. Myrapetra is the largest subgenus, currently with twenty-four valid species and fourteen subspecies, most of them allocated in the “P. occidentalis species-group”. Several species within Myrapetra are poorly characterized, with imprecise limits, and subspecies are largely based on color, that is highly variable feature, even among nest mates. This study is about those species of the P. occidentalis species-group which are morphologically more distinct from P. occidentalis (and its more similar neighbors), which we refer to as the species related to P. scrobalis and P. flavifrons. We describe a new species (P. rosalinae Amorim & Santos, sp. nov.) and for three subspecies we recognize the need to treat as distinct species (P. brevitarsus Richards, stat. nov.; P. hecuba Richards, stat. nov.; and P. surinama Richards, stat. nov.). In addition, we describe the males of two species and provide the first data (description and photos) on male genitalia of four taxa. P. dimorpha Richards, previously an isolated species within Myrapetra is treated as a member of the P. occidentalis species-group. Additionally, we provide a new identification key for the studied species.